Descriptions of three larvae of Osmylus species from Japan (Neuroptera: Osmylidae), with a proposed naming system for the larval sclerites - Matsuno, Shigetomi; Yoshitomi, Hiroyuki (Zootaxa, 2016)
The naming system of sclerites on osmylid larvae is proposed by observation of three Japanese osmylid species, Osmylus (Osmylus) hyalinatus McLachlan, 1875, O. (O.) pryeri McLachlan, 1875, and O. (Plesiosmylus) tessellatus McLachlan, 1875. The last instar larvae of the genus and species are described with biological notes and a key to the species. Osmylus kisoensis Iwata, 1928 is synonymized with O. (O.) pryeri McLachlan, 1875.